Protection of Intellectual Property Rights from the Perspective of Islamic Law and Legislation in Indonesia - Arminsyah, Arminsyah (UIN SYEKH ALI HASAN AHMAD ADDARY PADANGSIDIMPUAN, 2024)
This paper examines the existence of intellectual property rights (IPR) protection in the perspective of Islamic law and legislation in Indonesia. IPR protection is an important issue in the era of globalization, which requires harmony between national law and international legal principles. In the Indonesian context, in addition to referring to national legislation, this study also pays attention to how the principles of Islamic law view and regulate the protection of IPR. The research method used is qualitative with a normative and descriptive-analytical approach. The results show that Islamic law, although sourced from classical texts, has the flexibility to accommodate IPR protection through principles such as 'urf (custom), maslahat (benefit), and qiyas (analogy). Meanwhile, legislation in Indonesia has established a comprehensive range of rules to protect IPR, although its implementation still faces various challenges. This study concludes that there is significant harmony between Islamic law and Indonesian legislation in terms of IPR protection, which can be used as a basis for increasing the effectiveness of IPR protection in Indonesia.